AN ANALYSIS OF STUDENTS’ ERROR IN WRITING CONDITIONAL SENTENCES AT GRADE XI OF SMA SWASTA TAMANSISWA SUKADAMAI IN 2021/2022 ACADEMIC YEAR - Cindy Ilsavitri1, Susi Masniari Nasution (Universitas Asahan, 2022)
The objectives of this research were to find the error in student’s writing at Eleven Science 1 of SMA Swasta Tamansiswa Sukadamai. The subject of this research were 25 students of SMA Swasta Tamansiswa Sukadamai. The technique of collecting data used in this research were observation, interview and written test. The researcher used Dulay’s Theory to classify the types of Error. In this research found 4 types of error. Those were Addition, Omission, Misformation, Misordering. The precentage of frequency the error. It was addition(28,08%), omission (17,55%) misformation (29,83%), and misordering (21,06%). From all of the types, the highest frequent types of the error was misformation. Keywords: Conditional Sentence, Writing, Error